Profil Tingkat Kemampuan Berpikir Kreatif Mahasiswa Program Studi Pendidikan Matematika pada Mata Kuliah Trigonometri - Yulika Sinta; Uminastuti (JURNAL PENDIDIKAN, 2020)
This research aims to determine and describe the level of creativethinking ability of students of the Mathematics Education Study ProgramDepartment of Mathematics and Natural Sciences Faculty of Mathematicsof Palangka Raya on trigonometry subject. The results showed that thepercentage of students with TKBK 4; 3; 2; 1 and 0 were 10.35%; 17.24%;20.69%; 34.48% and 17.24%. When solving mathematics problem, studentshave TKBK 4 fulfill the aspects of very creative criteria; TKBK 3 fulfill ofthe aspects of fluency as well as the flexibility of the criteria of creativethinking because able to apply a concept or formula in different wayscorrectly and the calculations also correctly; TKBK 2 fulfill of aspectsflexibility of creative thinking criteria because able to provide an idea of adifferent way or solution but cannot be done properly so that calculation is errors; TKBK 1 fulfill the eloquence aspect of creative thinking criteriabecause able to solve problems using one method or solution correctly andunable to provide a different way; TKBK 0 is unable to fulfill any aspect ofthe three criteria of creative thinking because unable to solve problems.